PEREMPUAN DAN KOPERASI (Studi Model Pemberdayaan Perempuan Melalui KWSU Setia Budi Wanita Malang) - Endang Hernanik (MUWAZAH : jurnal kajian gender, 2010)
This descriptive qualitative study aimed to know the model of empowerment of women by the KWSU Setia Budi Wanita Malang and success empowerment model conducted by the Cooperative. The research source was collected both primary and secondary acquired through in-depth interviews, documentation and observation. Research results show that, the model Women’s Empowerment KWSU Setia Budi Wanita Malang is accountability group system model string. The success of the empowerment model KWSU Setia Budi Wanita Malang is located on the board, management, programs, builder, and the group itself. They understand very well about the rules of the cooperative and its execution, each job description is not related in a personal, participatory management and programs to suit the needs of society and of the spirit of behavior change.